MENGGUGAT OTENTISITAS KEUANGAN SYARIAH KONTEMPORER: ANALISIS KRITIS BERBASIS MAQASID AL-SHARIAH DAN EKONOMI POLITIK GLOBAL - Sri Dewi Yusuf; Ismail Makuta; Sekar Laras Ayu (Smart Education, 2026)
This study criticizes the authenticity of contemporary Islamic financial practices through the lenses of maqasid al-shariah and global political economy. While Islamic finance is often positioned as an ethical alternative to conventional finance, a fundamental question arises: do its practices truly represent substantive Shariah principles, or are they merely structural replications of global capitalism with a Shariah label. Using a qualitative-critical method with discourse analysis and a normative maqasid al-shariah approach, this study examines regulatory documents, Islamic banking practices, and political economy literature. The findings reveal that Islamic finance frequently emphasizes formalistic compliance with fiqh (jurisprudence) while neglecting core ethical-social goals like distributive justice, wealth gap reduction, and poverty alleviation. Furthermore, its integration into neoliberal global economics exposes a contradiction between normative rhetoric and empirical reality. In the context of Indonesia and the digital economy, Islamic finance has failed to address structural issues such as automation-driven unemployment, platform economy labor shifts, and unequal digital capital access. The study concludes that Islamic finance requires a paradigm reformulation to avoid becoming a mere variant of financial capitalism, transforming instead into an instrument for a just, sustainable economy